Pituitary metastasis of hepatocellular carcinoma as the initial presentations: a case report and review of the literature - He, Qiang; Deng, Feng; Cai, Bowen; You, Chao; Zheng, Songping (Frontiers in Oncology, 2023)
Background Extrahepatic metastasis of hepatocellular carcinoma (HCC) is common. However, pituitary metastasis of HCC is extremely rare. Our case may be helpful to extend the understanding of the disease. Case presentation A 65-year-old man presented to the outpatient department for unexplained headache and ptosis for 1 month. Brain imaging showed a slight enhancement tumor in the pituitary fossa, and the endocrinological assessment showed normal results. We considered the tumor as a non-functioning pituitary adenoma before surgery. Then, the tumor was resected by an endonasal endoscopic transsphenoidal approach. The histopathological examination results revealed the pituitary metastasis of HCC. Additional abdominal imaging revealed tumors were located in the left and right liver lobes with portal vein invasion and bilateral ilium metastases. After multidisciplinary cooperation, the patient chose chemotherapy. Conclusion We report a case of HCC metastasis to the pituitary gland that initially presented with neurological symptoms. We should consider the possibility of pituitary metastasis in HCC patients.